Treatment of early rheumatoid arthritis. Issue 4 (July 2005) - Raza, Karim; Salmon, Mike; Buckley, Christopher D
Rheumatoid arthritis is common and leads to joint damage due to persistent synovitis. Aggressive treatment within the first few  years after symptom onset, with either disease-modifying antirheumatic drugs or antitumor necrosis factor therapy, reduces the rate of disease progression. There is increasing interest in the concept that the first few  months after symptom onset represent a pathologically distinct phase of disease and that this translates into a therap eutic window of opportunity during which it may be possible to switch off the disease process. The rationale for, and difficulties associated with, treatment within this window are discussed.